Step-by-step explanationgiven the equation:
![Hg=((j+a)/(4))](https://img.qammunity.org/2023/formulas/mathematics/college/j2xsw6kfi781ryncx7f4a8twbbgzd6amtj.png)
An equation is a mathematical expression that contains an equals symbol where one or more values are unknown ,
to solve for a, we need to isolate it , to do this we can use some properties
so
Step 1
a)The multiplication property of equality states that when we multiply both sides of an equation by the same number, the two sides remain equal, so to remove the 4 in the denominator, we can multiply both sides by 4
![\begin{gathered} Hg=((j+a)/(4)) \\ multiply\text{ both sides by 4} \\ Hg*4=((j+a)/(4))*4 \\ 4Hg=(j+a)((4)/(4)) \\ 4Hg=(j+a)(1) \\ 4Hg=(j+a) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rhdk81cxcp1py51xbhw4qixzjy1pit5uw4.png)
Step 2
now, we need to "move the j to the left", to do that subtract j in both sides, The subtraction property of equality states that when the same number is subtracted from both sides of an equality, then the two sides of the equation still remain equal, so
![\begin{gathered} 4Hg=(j+a) \\ subtract\text{ j in both sides } \\ 4Hg-j=(j+a)-j \\ 4Hg-j=a \\ a=4Hg-j \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qt8s2cde49c65w1mfemmvath4ph15a2nwm.png)
therefore, the answer is
![a=4Hg-j](https://img.qammunity.org/2023/formulas/mathematics/college/drl5dj2o5vvfl3zr7ewl9gq990f2azidfv.png)
I hope this helps you